2019
DOI: 10.1021/acschembio.8b01018
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting CD22 To Selectively Tolerize Autoantibody Producing B-Cells in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease that primarily affects the synovial joints and can lead to bone erosion and cartilage damage. One hallmark of RA is anti-citrullinated protein autoantibodies (ACPA) and memory citrulline-specific B-cells, which have been implicated in RA pathogenesis. While depletion of B-cells with Rituximab improves clinical responses in RA patients, this treatment strategy leaves patients susceptible to infections. Therefore, using Siglecengaging Tolerance-inducing Antigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 80 publications
(146 reference statements)
0
35
0
Order By: Relevance
“…Administration of recombinant FVIII in previously STAL-tolerized FVIII-deficient mice - a mouse model for hemophilia A [98] - prevented the production of anti-FVIII antibodies, which subsequently enabled the delivery of FVIII to prevent bleeding in a tail clip assay. Two recent studies further illustrated the effectiveness of CD22 targeting-STALs in tolerizing B cells reactive towards 2S albumin (Ara h 2; the major peanut allergen) and citrulline, which are two antigens implicated in peanut allergy and rheumatoid arthritis, respectively [99], [100]. The latter of these studies suggested it is possible to induce tolerance in human antigen-specific B cells since STALs bearing a citrullinated antigen prevented the formation of anti-citrulline antibodies upon a subsequent in vitro challenge.…”
Section: Roles Of Glycan Ligands In Controlling Cd22 As a Bcr Inhibitmentioning
confidence: 99%
“…Administration of recombinant FVIII in previously STAL-tolerized FVIII-deficient mice - a mouse model for hemophilia A [98] - prevented the production of anti-FVIII antibodies, which subsequently enabled the delivery of FVIII to prevent bleeding in a tail clip assay. Two recent studies further illustrated the effectiveness of CD22 targeting-STALs in tolerizing B cells reactive towards 2S albumin (Ara h 2; the major peanut allergen) and citrulline, which are two antigens implicated in peanut allergy and rheumatoid arthritis, respectively [99], [100]. The latter of these studies suggested it is possible to induce tolerance in human antigen-specific B cells since STALs bearing a citrullinated antigen prevented the formation of anti-citrulline antibodies upon a subsequent in vitro challenge.…”
Section: Roles Of Glycan Ligands In Controlling Cd22 As a Bcr Inhibitmentioning
confidence: 99%
“…Therapeutic treatment of K/BxN mice with GPI-LP-CD22L and PLGA-R, after disease onset, when anti-GPI IgG1 titers had increased, showed prevention and, in some cases, even reversal of disease. Together results suggest the potential of the combined treatments to treat early stage autoimmune diseases, particularly in view of the fact that STALs have been demonstrated to suppress antigen specific human memory B cells from rheumatoid arthritis patients 24 , and that B cell depleting therapy such as rituximab (anti-CD20) is therapeutically effective in a rheumatoid arthritis setting 46 47 . Co-delivery of OVA-STALs (OVA-LP-CD22L) and PLGA-R nanoparticles induce greater tolerance to liposomal OVA than either nanoparticle alone.…”
Section: Discussionmentioning
confidence: 95%
“…This engagement leads to a potent apoptotic signal resulting in elimination of antigen-reactive B cells, leaving the rest of the B cell repertoire unaffected, and induction of B cell tolerance due to depletion of the antigen-specific B cells 21 . The utility of Siglec tolerizing antigenic liposomes (STALs) has been successfully demonstrated in several models of disease, one involving the generation of inhibitory antibodies to FVIII in hemophilia mice 18 , another involving tolerization of animals to allergen sensitization in a peanut antigen anaphylaxis model 22 23 , and a third involving apoptosis of autoantigen-specific memory B cells from RA patients 24 . STALs are particularly effective in naïve animals since there is minimal activation of CD4+ T cells that are required for B cells to differentiate into cells that produce high affinity antibodies of the IgG class, and are less suitable for inducing tolerance in animals with an ongoing immune response with antigen specific CD4+ T helper or T memory cells.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed a reduction in fibrinspecific B cells in the presence of both bifunctional NPs and human sera, but not in heat-inactivated human sera [157], suggesting that the bifunctional NPs were indeed inducing complement-mediated death of fibrin-specific B cells. In a similar precision-based design that targets autoreactive B cells, Bednar et al [158] fabricated a liposome conjugated with (1) a high-affinity glycan ligand for the inhibitory B cell receptor, CD22, and (2) a cyclic citrullinated peptide, to facilitate interaction with B cells specific for this autoantigen. Upon B cells encountering this dual-functionalized liposome, the glycan ligand engages CD22 and induces B cell deletion, subsequently restoring B cell tolerance towards the citrullinated antigen [158].…”
Section: B Cellsmentioning
confidence: 99%
“…In a similar precision-based design that targets autoreactive B cells, Bednar et al [158] fabricated a liposome conjugated with (1) a high-affinity glycan ligand for the inhibitory B cell receptor, CD22, and (2) a cyclic citrullinated peptide, to facilitate interaction with B cells specific for this autoantigen. Upon B cells encountering this dual-functionalized liposome, the glycan ligand engages CD22 and induces B cell deletion, subsequently restoring B cell tolerance towards the citrullinated antigen [158]. Bednar and co-authors demonstrated that this liposome was able to induce tolerance in autoreactive B cells isolated from RA patients, as well as in SJL/J mice immunized against cyclic citrullinated peptides [158].…”
Section: B Cellsmentioning
confidence: 99%